The integrated inventory and production planning for time-varying demand process / Siti Suzlin Supadi - Siti Suzlin, Supadi (2012)
In the literature, integrated inventory model has received a lot of attention. Most previous works on this topic have been based on the assumption of constant demand rate. However this assumption is not reliable in reality; it is either increasing or decreasing with time. In this thesis, we considered the model which consists of a single vendor who manage the production and deliver to a single buyer with a linearly decreasing demand rate over a finite time horizon. Costs are attached to manufacturing set up, the delivery of a shipment and stockholding at the vendor and buyer. The objective is to determine the number of shipments and size of those shipments which minimize the total system cost - assuming the vendor and buyer collaborate and find a way of sharing the consequent benefits. We begin this thesis with the integrated inventory policy for shipping a vendor’s final production batch to a single buyer under linearly decreasing demand. The first case considered here is the holding cost at the vendor is less than at the buyer. We solve this model with equal shipment sizes policy, equal shipment periods policy and unequal shipment sizes and unequal shipment periods policy. Then, we develop a mathematical model when the unit holding cost is higher at the vendor rather than at the buyer (consignment stock problem). For this case, we also consider equal shipment sizes policy, equal shipment periods policy, and unequal shipment sizes and unequal shipment periods as in the previous case policy. It is followed by an integrated inventory model with n production batches which consists of the final batch at the end of the production cycle. This model also considers the case of the buyer’s holding cost being greater than the vendor’s and vice versa. We consider this model with equal cycle time and unequal cycle time for both policies. We show the solution procedure when the shipment sizes are equal and when they are unequal. We solve all the models in this thesis using Microsoft Excel Solver and illustrate all the policies with numerical examples and sensitivity analysis. Then we make some comparison of the model. Lastly we end the thesis with conclusion and some recommendations for further research.